2020
DOI: 10.1016/j.erss.2020.101642
|View full text |Cite
|
Sign up to set email alerts
|

Novel or normal? Electric vehicles and the dialectic transition of Nordic automobility

Abstract: Over the last decade or more, the automobility literature has sought to observe and affect the dynamic tenacity of passenger vehicles. This paper takes up a recent call to actually study how private electric vehicles (EVs) are changing automobility. For this, it identifies four qualitative categories of automobility: general vehicle use, the car in daily life, vehicle symbolism and the effects of electrification. We study how these categories are affected by electric vehicles based on original data we gathered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 62 publications
0
13
0
1
Order By: Relevance
“… AlSabbagh et al, 2017 , Akin and Kara, 2020 , Berrittella et al, 2008 , Boon and van Wee, 2017 , Charanwanitwong and Fraszczyk, 2018 , Citroë n, 2020 , Darcy and Burke, 2018 , EIT, 2020a , EIT, 2020b , Epstein and Givoni, 2016 , Goletz et al, 2020 , Hart et al, 2009 , Hirschhorn et al, 2018 , Jain et al, 2014 , Jittrapirom et al, 2018 , Kattirtzi and Winskel, 2020 , Kester et al, 2018 , Kester et al, 2020 , Krause et al, 2016 , Krause et al, 2020 , Lyons and Davidson, 2016 , Melander et al, 2019 , Munira and Santoso, 2017 , Nogué s et al, 2020 , Noel et al, 2019 , Potter et al, 1999 , Salmon et al, 2019 , Shakibaei et al, 2020 , Shiftan et al, 2003 , Stamos et al, 2016 , Sovacool et al, 2018a , Sovacool et al, 2018b , Suman et al, 2017 , Sureeyatanapas et al, 2018 , Tennø y et al, 2015 , The Economist Intelligence Unit, 2020 , Ãœlengin et al, 2018 , Valero-Gil et al, 2018 , Van der Pas et al, 2012a , Van der Pas et al, 2012b , Van Ristell et al, 2013 , Varho et al, 2013 , Workman et al, 2020 , Xenias and Whitmarsh, 2013 , Xylia and Silveira, 2017 , Zhang et al, 2020c , Zubaryeva et al, 2012 .…”
Section: Uncited Referencementioning
confidence: 99%
“… AlSabbagh et al, 2017 , Akin and Kara, 2020 , Berrittella et al, 2008 , Boon and van Wee, 2017 , Charanwanitwong and Fraszczyk, 2018 , Citroë n, 2020 , Darcy and Burke, 2018 , EIT, 2020a , EIT, 2020b , Epstein and Givoni, 2016 , Goletz et al, 2020 , Hart et al, 2009 , Hirschhorn et al, 2018 , Jain et al, 2014 , Jittrapirom et al, 2018 , Kattirtzi and Winskel, 2020 , Kester et al, 2018 , Kester et al, 2020 , Krause et al, 2016 , Krause et al, 2020 , Lyons and Davidson, 2016 , Melander et al, 2019 , Munira and Santoso, 2017 , Nogué s et al, 2020 , Noel et al, 2019 , Potter et al, 1999 , Salmon et al, 2019 , Shakibaei et al, 2020 , Shiftan et al, 2003 , Stamos et al, 2016 , Sovacool et al, 2018a , Sovacool et al, 2018b , Suman et al, 2017 , Sureeyatanapas et al, 2018 , Tennø y et al, 2015 , The Economist Intelligence Unit, 2020 , Ãœlengin et al, 2018 , Valero-Gil et al, 2018 , Van der Pas et al, 2012a , Van der Pas et al, 2012b , Van Ristell et al, 2013 , Varho et al, 2013 , Workman et al, 2020 , Xenias and Whitmarsh, 2013 , Xylia and Silveira, 2017 , Zhang et al, 2020c , Zubaryeva et al, 2012 .…”
Section: Uncited Referencementioning
confidence: 99%
“…Kester et al recently refer to this as the “dialectic” nature of future sustainability transitions, given they can reinforce dominant practices as much as they can reform existing ones [30] . Even electric mobility, an innovation Kanda and colleagues noted may ultimately be less affected by the pandemic, has unclear and highly differentiated impacts on sustainability as noted in Table 1 .…”
Section: Implications For Social Practices and Sustainability Transitmentioning
confidence: 99%
“… EVs are co-opted and marginalized by transnational conglomerates with little desire for social change. Source: Authors modification from Kester et al [30] . …”
Section: Implications For Social Practices and Sustainability Transitmentioning
confidence: 99%
“…The European Environment Agency (EEA) [15] reported that 22.5% of all new cars sold in Norway in 2015 were electric. In [16], an analysis found that respondents were equal in percentage for gender and age: <25 (18.2%), 25…”
Section: Finding Early Adoptersmentioning
confidence: 99%
“…(2) The was a lack of regime patchworking initiatives; rather, initiatives mainly supported alternative fuels and PHEVs, opposing BEVs. For the cognitive dimension, it is important to explain the differences between Stockholm and Oslo, in which a greater prominence of BEVs is highlighted, since EVs are easily recognizable by their license plates [16]. (3) A lack of wide scenario policies: policy directions, visions and economic incentives confuse users, who do not know if private vehicles or collective ones will be supported in the coming years.…”
Section: Chicken or Egg Paradoxmentioning
confidence: 99%